Does vestibular rehabilitation improve postural control of subjects with chronic subjective dizziness? - Baydan, Mine; Yigit, Oznur; Aksoy, Songul (PloS one, 2020)
Postural control is the ability to maintain equilibrium and orientation in a gravitational environment. Patients with chronic subjective dizziness have some troubles with their postural stability. The present study aimed to assess the benefit of home-based vestibular rehabilitation in patients with chronic subjective dizziness using computerized dynamic posturography. Therefore, 100 subjects, between 19 to 86 years, diagnosed with dizziness were included in the study. Computerized dynamic posturography was performed to assess postural stability. Vestibular rehabilitation programs included exercises tailored to the particular needs of each patient. After vestibular rehabilitation, patients were re-examined using the same tests. Posturographic data were analyzed and compared for before and after vestibular rehabilitation findings. The mean composite scores before the intervention (58,92 ±11,64) was significantly (p<0.01) lower than the mean composite scores after vestibular rehabilitation (73,83 ± 8,26). This result is found to be statistically significant. In conclusion it could be suggested that the effectiveness of vestibular rehabilitation could be verified by means of computerized dynamic posturography as a concrete method.